2023
DOI: 10.16910/jemr.16.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of task difficulty on gaze behaviour during landing with visual flight rules in low-time pilots

Abstract: Eye movements have been used to examine the cognitive function of pilots and understand how information processing abilities impact performance. Traditional and advanced measures of gaze behaviour effectively reflect changes in cognitive load, situational awareness, and expert-novice differences. However, the extent to which gaze behaviour changes during the early stages of skill development has yet to be addressed. The current study investigated the impact of task difficulty on gaze behaviour in low-time pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…First, the current study specifically focused on pilots with their Private Pilots’ License (PPL) or Commercial Pilots’ License (CPL). Earlier work demonstrated that there is a significant learning curve that occurs within the ab-initio stage of skill development that is associated with more variability around the performance and gaze measures of interest that may go unexplained and impact our conclusions ( 5 ). Furthermore, the use of high-fidelity flight simulators has been shown to immediately diminish the performance of ab-initio pilots who are unfamiliar with the immersive cockpit environment ( 38 ).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…First, the current study specifically focused on pilots with their Private Pilots’ License (PPL) or Commercial Pilots’ License (CPL). Earlier work demonstrated that there is a significant learning curve that occurs within the ab-initio stage of skill development that is associated with more variability around the performance and gaze measures of interest that may go unexplained and impact our conclusions ( 5 ). Furthermore, the use of high-fidelity flight simulators has been shown to immediately diminish the performance of ab-initio pilots who are unfamiliar with the immersive cockpit environment ( 38 ).…”
Section: Introductionmentioning
confidence: 85%
“…Eye tracking can help reveal these differences through the examination of other basic and dynamic gaze metrics that provide further insight into how efficiently individuals process information and could reveal the differing levels of task demands associated with a particular scenario. For example, previous work has shown that more efficient information processing is associated with reduced fixation duration ( 3 ; 12 ; 26 ; 40 ; 50 ; 52 ; 64 ), increased fixation frequencies ( 12 ; 25 ; 26 ; 28 ; 40 ; 64 ), as well as a greater propensity to fixate more task-relevant areas of interest (AOIs) - greater fixation dispersion (i.e., Stationary Gaze Entropy: SGE) - in a more variable/flexible pattern; as made apparent with greater fixation sequence complexity (i.e., Gaze Transition Entropy: GTE) ( 6 ; 5 ; 4 ; 26 ; 28 ; 40 ; 50 ). Several studies have also demonstrated how reduced blink rate is a reliable proxy for increased task difficulty as well as cognitive load ( 26 ; 40 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations